Romans : a commentary - Jewett, Robert (Hermeneia--a critical and historical commentary on the Bible., 2007)
Deeply conversant in the full range of questions and interpretations of the letter, Jewett's commentary explores the crucial and controverted passages that have always animated studies of Romans.